Circulating tumour-derived microvesicles in plasma of gastric cancer patients - Baran, Jaroslaw; Baj-Krzyworzeka, Monika; Weglarczyk, Kazimierz; Szatanek, Rafal; Zembala, Maria; Barbasz, Jakub; Czupryna, Antoni; Szczepanik, Antoni; Zembala, Marek (Cancer Immunology, Immunotherapy, 2010)
Cell membrane microfragments called microvesicles (MV) originating from different cells are circulating in the blood of healthy subjects and their elevated numbers are found in different diseases, including cancer. This study was designed to characterise MV present in plasma of gastric cancer patients. Since majority of MV in blood are platelets-derived (PMV), plasma samples deprived of PMV were used. In comparison to control, the number of MV in patients was significantly elevated in all stages, higher in more advanced disease. Patients’ MV showed an increased membrane expression of CCR6 and HER-2/neu. The proportion of MV carrying some leucocyte determinants was low and similar in patients and control. Transmission electron microscopy showed their substantial heterogeneity in size and shape. The size determined by dynamic light scattering analysis confirmed this heterogeneity. The MV size distribution in patients was broader within the range of 10–800 nm, while in control MV showed 3-mode distribution within the range of 10–400 nm. Atomic force microscopy confirmed MV size heterogeneity with implication that larger objects represented aggregates of smaller microparticles. Patients’ MV exhibited increased absolute values of zeta potential, indicating a higher surface charge. Tumour markers HER-2/neu, MAGE-1, c-MET and EMMPRIN were detected both in control and patients’ samples with stronger expression in the latter. Significantly higher expression of MAGE-1 and HER-2/neu mRNA was observed in individual patients. All together, it suggests that at least some MV in plasma of gastric cancer patients are tumour-derived. However, their role in cancer requires further studies.